2011
DOI: 10.1111/j.1365-2494.2011.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Damage to roots of Trifolium subterraneum L. (subterranean clover), failure of seedlings to establish and the presence of root pathogens during autumn–winter

Abstract: Field-based plant bioassays were employed to assess the potential for pre-and post-emergence loss of seedlings and for root damage affecting Trifolium subterraneum L. (subterranean clover) during autumn-winter at 17 pasture sites across a broad agricultural area of temperate southern Australia. Between 9 and 93% (median 21%) of T. subterranean seedlings failed to emerge at the 14 locations where soil moisture was considered adequate for germination. Post-emergence losses were lower (range 0-32%; median 7%). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…The association found between clade F Pythium and clover disease is supported by work in Australia. Using the same detection system, Simpson et al (2011) found the DNA concentration of clade F Pythium to have a linear relationship with damage to Trifolium subterraneum (subterranean clover) across multiple sites in Australia. This reinforces the importance of these pathogens in limiting production in pastoral agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association found between clade F Pythium and clover disease is supported by work in Australia. Using the same detection system, Simpson et al (2011) found the DNA concentration of clade F Pythium to have a linear relationship with damage to Trifolium subterraneum (subterranean clover) across multiple sites in Australia. This reinforces the importance of these pathogens in limiting production in pastoral agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these are primarily pathogenic to cereal crops and are included as part of the DNA-based pathogen testing provided to grain growers in southern Australia (Simpson et al 2011). While some of the Pratylenchus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The Predicta B DNA extraction service infers P. irregulare quantification through quantification of Pythium Clade F as conducted and reported in other studies involving this pathogen on forage legumes (e.g. Simpson et al, 2011). Assays included controls to check for contamination and PCR inhibition.…”
Section: Composition Studymentioning
confidence: 99%
“…Climatic conditions, especially precipitation during the growing season, are undoubtedly the most important factor (Bolger et al 1993), but soil fertility (Saul et al 1999), competition with other plant species (Conning et al 2011), shading levels (Kyriazopoulos et al 2012), livestock management (Ates et al 2013), and pest and diseases (Simpson et al 2011) can also have an important influence on these parameters.…”
Section: Introductionmentioning
confidence: 99%